Nutritional metabolomics and their implications in clinical studies - Türkoğlu, Semra (Nova Science Publishers, Inc., 2023)
Metabolomics deals with small molecule metabolites, and one of their main purposes is to identify those small molecules that make differences in the metabolic effects of different diets. Thus, deepening our knowledge of the interactive and regulatory roles of human health and nutrition. Metabolomics, pharmacology, and toxicology have also been widely adopted, but they are relatively new to human nutrition. Today, scientists play an important role in the health status of people by finding new bioactive food components that prevent cancer, obesity, diabetes, cardiovascular and chronic diseases, as well as prolong life and improve physical and mental health. In this context, the use of high-throughput metabolomics techniques contributes to the development of nutritional models, the benefits of a diet to metabolism, and the improvement of physiological responses to this diet. That is, it provides a better understanding of the effects of genes, enzymes, proteins, metabolites, and microenvironments at the cellular level. Metabolomics can assist in the design of nutritional programs and improve our understanding of nutrition and the role of nutrients in promoting and maintaining cellular functions and overall health. The purpose of this section is to make a general assessment of nutritional metabolomics, to emphasize the effects of nutritional metabolomics on clinical studies, and to contribute to the scientific literature on these issues. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Clinical studies; Metabolites; Nutritional metabolomics